INSECT CELLS AS HOSTS FOR RECOMBINAT PROTEINS - Retno Murwani (JOURNAL OF COASTAL DEVELOPMENT, 1997)
Since the development of recombinant baculovirus expression system, insect cell culture has rapidly gain popularity as the method of choice for production of a variety of biologically active proteins. Up to date tens of recombinant protein have been produced by this method commercially or non-commercially and have been widely used for research. This review describes the basic concept of baculovirus expression vector and the use of insect cells as host for recombinant proteins. Examples of the recombinant proteins produced by this system are given.